Glioma-initiating cells at tumor edge gain signals from tumor core cells to promote their malignancy - Soniya Bastola (Nature Portfolio, 2020)
Intratumoural spatial heterogeneity is crucial to enhance therapeutic resistance in glioblastoma. Here, the authors show a paracrine signaling mechanism where glioblastoma-initiating cells located in the tumour edge elevate their malignancy by interaction with core-located tumour cells.